The effect of individual characteristics and supervision experiences on the perceived quality of the supervision relationship - Wodahl, Eric J. (Criminal justice policy review, 2021)
Research has shown that high-quality relationships between individuals on probation/parole and their supervising officers can reduce recidivism and increase compliance. Although this relationship clearly matters, little attention has been given to understanding the factors that influence this relationship. Drawing on research in psychology and counseling, this study explores how both individual characteristics and supervision experiences affect the perceived quality of the supervision relationship. Results from the Serious and Violent Offender Reentry Initiative (SVORI) reveal that both individual characteristics—such as mental health and family support—and supervision experiences—such as the use of sanctions and incentives—exert significant effects on the supervision relationship. Yet, the effects of supervision experiences were substantially more robust than the individual characteristics. Findings suggest community supervision agencies should prioritize positive supervision experiences to build positive relationships between the returning person and supervising officer.